The First Record of Atractosteus spatula (Lacepède, 1803) (Actinopterygii: Lepisosteiformes: Lepisosteidae) in the Klawing River, Central Java, Indonesia - Taufik Budhi Pramono; Sri Marnani; Joni Johanda Putra; Saprudin; R Adharyan Islamy (Jurnal Penelitian Pendidikan IPA, 2024)
The Alligator gar, Atractosteus spatula (Lacepède, 1803), is a high-predatory fish native to North America. In 2020, two specimens were captured as a new species in the public waters of Klawing River, Central Java, Indonesia at 7°'19’.27"S 109°20'10"E. Therefore, this study aims to describe the meristic and morphometric features of Atractosteus spatula based on an in-situ observation in the river.